A review of post-dates induction of labour research: a critical discourse analysis. (September 2022) - Shorter, Ms Beth; Newnham, Elizabeth; Allen, Jyai
Abstract : Problem: Despite equivocal evidence, induction of labour (IOL) for post-dates pregnancy is an increasingly common birth intervention that impacts well women and their babies. Birth interventions can cause iatrogenic harm to mothers and babies. Recent evidence shows that routine post-dates IOL does not reduce the chance of stillbirth. Background: Previous studies have shown how assumptions and beliefs within biomedical discourse filter into medical research. Discourse influences clinical practice guidelines, policies and how information is communicated to women. Methods: We used Foucauldian discourse analysis to critically analyse the biomedical literature on IOL, adding to current knowledge about both the intervention itself and how it is shaped by medical discourse. We purposively sampled biomedical, quantitative research on IOL, published in the last five years, using key search terms. Twelve studies met the criteria. Findings / Results: In this presentation, we show how current biomedical literature concerns itself with "the dangerousness of [prolonged] pregnancy", which prioritises the safety of the fetus, while maintaining a narrative that post-dates IOL is "safe and necessary", despite this not necessarily being the case, at least not for every woman. This exposes the "invisibility of women" in the research and practice of IOL for post-dates. Discussion: We juxtapose these discourses and extend our findings, drawing on current qualitative literature to demonstrate how women's experiences reflect these medical assumptions, feeling that IOL is inevitable, or that they do not have a choice. This is concerning, because although constructed as a "safe" intervention, it is not without risk, and raises questions about informed consent. Conclusion: There is increasing concern about overmedicalisation of birth. Critiquing the dominance of obstetric knowledge claims is important to give space for women's voices, to recognise other forms of knowledge and to humanise birth.